Effects of low-calcium solution on calcium phosphate metabolism in CAPD patients - DUAN Li-ping; ZHENG Zhao-xia; HU Tian-xiao (Linchuang shenzangbing zazhi)
Objective To observe the effects of physiological calcium dialysate(Dianeal PD4)on the serum calcium,serum phosphorus and intact parathyroid hormone(iPTH) in peritoneal dialysis patients in Handan area.Methods The clinical data of 77 patients diagnosed as having end-state renal disease(ESRD) for the first time and hospitalized in our hospital from February 2006 to March 2014 were analyzed retrospectively.These patients were treated with physiological calcium dialysate(1.25mmol/L) in combination with oral calcium and active vitamin D for continuous ambulatory peritoneal dialysis(CAPD).The changes in serum calcium,phosphorus,iPTH,alkaline phosphatase(ALP),albumin,total protein,urea,creatinine and uric acid were observed in patients after dialysis for 3,6and 12 months.The indices of adjusted serum calcium,phosphorus,iPTH,and ALP were analyzed before and after dialysis,and the discomforts such as hypotension,twitch,restless legs,and pruritus were observed at the same time.Results The indices of serum calcium,serum phosphorus,urea,creatinine,uric acid,total protein,and hemoglobin level in CAPD patients treated with physiological calcium dialysate for 3,6 and 12 months showed significant difference before and after dialysis(P<0.05).However,no statistically significant differences in these indices were found among patients dialyzed for 3,6 and 12 months(P>0.05).The level of iPTH was increased gradually,with a significant difference before and 12 months after dialysis(P<0.05).No significant difference in the level of iPTH was found before and 3 or 6 months after dialysis(P>0.05).There was no significant difference in serum ALP and total protein before and after dialysis.Conclusions Treatment of CAPD patients in Handan area with physiological calcium dialysate,in combination with oral calcarea carbonica and active vitamin D,can effectively improve the calcium and phosphorus metabolism disorder,thereby preventing the occurrence of secondary hyperparathyroidism and renal bone disease.